Analisis Kondisi Sosial Ekonomi Rumah Tangga Petani Tembakau di Desa Batu Nampar Kecamatan Jerowaru - Muhamad Zaril Gapari (ISLAMIKA, 2020)
Rural communities are communities that live in the same area , which are united and together, have strong ties and greatly influence one another. This is because the traditional village community is still very strong and thick. In general, village communities are identified with farming communities, this is because rural communities are predominantly making a living from agricultural products which are poor farmers whose livelihoods are below the poverty line. This shows a very large gap from urban communities . This study aims to determine the socioeconomic conditions of tobacco farm households in the village Batu Nampar Jerowaru District . The problem to be investigated is the effect of tobacco farming on the level of income of the farming community. This type of research is a descriptive study in which the population is 415 farm households with a sample of 25 people using purposive sampling techniques. While the data collection techniques used in this study are direct interview techniques based on a list of questions that have been prepared previously. Based on the results of research and data analysis, the gross income of Rajang tobacco farmers is Rp. 90,230,000. the total cost spent by farmers during one growing season is Rp. 33,854,000 with an average of Rp. 1,354,000. Net income of Rajang tobacco farmers after deducting costs by Rp. 56,376,000 with an average income of Rp. 2,255,040. Judging from the indicators of welfare and based on the reference to the level of welfare from the three aspects measured namely housing, education, and health, the average respondent farmer is in the welfare category even though there are still some who are not yet prosperous. Where the pre-prosperous category is 7 people, prosperous I are 11 people, prosperous II is 5 people, prosperous III is 2 people and none of them have reached Prosperous III Plus.